THE ISSUES OF INNOVATIVE AND INVESTMENT DEVELOPMENT OF INDUSTRIAL ENTERPRISES UNDER CONTEMPORARY CONDITIONS - Lesko, O. Y.; Prychepa, I. V. (Visnyk of Vinnytsia Politechnical Institute, 2016)
There had been researched the state of innovative and investment development of industrial enterprises under contemporary conditions. There had been analyzed the dynamics of the basic indexes of innovative and investment activities in Ukrainian industry. There had been determined the main issues of innovative and investment development of domestic industrial enterprises under modern conditions. There had been determined the basic directions for the solution of the problems identified.